Implementasi Model Pembelajaran Cooperative Integrated Reading And Composition (CIRC) Untuk Meningkatkan Keterampilan Menulis Ringkasan Pada Siswa Kelas V SDN 2 Nyuhtebel - Ni Wayan Lusiani (Jayapangus Press, 2019)
This research was conducted at SDN 2 Nyuhtebel in Class V where the ability of students for Indonesian subjects especially summary writing skills was quite low. This study aims to improve the results of writing summary skills using Cooperative Integrated Reading and Composition (CIRC) learning models for fifth grade students of SDN 2 Nyuhtebel. In the Indonesian Language class V students who have not been able to reach the KKM that has been determined by the teacher. This type of research is classroom action research. The subjects in this study were the fifth grade students of SDN 2 Nyuhtebel, totaling 17 students. Data collection techniques in this study through evaluation and observation tests during the learning process. Analysis of the data in this study used descriptive qualitative to explain the observation sheet and quantitative to explain the results obtained by students. The results of the study are that the use of Cooperative Integrated Reading and Composition (CIRC) learning models can improve the results of summary writing skills in fifth grade students of SDN 2 Nyuhtebel as follows: initial conditions or pre-action average results of writing summary skills reach 67.29 with completeness 17 , 65% of 3 students with a score above the specified KKM was 75 then given action in cycle I an increase of 6.42 the difference was calculated from the average results of the writing skills summary cycle I reached 73.71 with completeness of 52.94% out of 9 new children reaching a value of ≥ 75 that has been set, because it has not reached ≥75% then the action is continued in cycle II, where there is a significant increase in the average value of the results of writing summary skills that is 78.29 with completeness 94.12% of 17 students, 16 students who achieved ≥ 75 results with conditions in the first cycle were 73.71. So the action is stopped in the second cycle because completeness has been achieved ≥ 75%.